2021
DOI: 10.1002/btpr.3198
|View full text |Cite
|
Sign up to set email alerts
|

Exometabolome profiling reveals activation of the carnitine buffering pathway in fed‐batch cultures ofCHOcells co‐fed with glucose and lactic acid

Abstract: Adjustments to CHO cell physiology were recently observed during implementation of a Raman spectroscopy‐based glucose and lactate control strategy. To further understand how these cells, under monoclonal antibody (mAb) production conditions, utilized the extra lactic acid fed, we performed a comprehensive semi‐quantitative and time‐dependent analysis of the exometabolome. This study focused on the CHO cell's metabolic shift from the fifth day of culture. We compared relative levels of extracellular metabolites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…It has been shown that the oxidation of lactate to pyruvate balances the intracellular redox state to maintain the rate of oxidative phosphorylation, so changes in the intracellular redox state are directly influenced by the competition between glycolysis and oxidative phosphorylation 37 . The NAD + /NADH ratio, and intracellular pyruvate level are the driving forces for the switch from aerobic glycolytic metabolism to hyperoxidative metabolism in CHO cells, and changes in lactate levels vary with these parameters 44,45 . Usually, in the rapid glycolysis stage, the reducing power NADH is continuously generated, and the reduction of pyruvate to lactate can quickly balance the intracellular redox state to maintain the rate of glycolysis; when the rate of oxidative phosphorylation is rapid, intracellular NADH continuously enters the mitochondria to provide reducing power, and redox balance is then maintained by the consumption of lactate to produce NADH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the oxidation of lactate to pyruvate balances the intracellular redox state to maintain the rate of oxidative phosphorylation, so changes in the intracellular redox state are directly influenced by the competition between glycolysis and oxidative phosphorylation 37 . The NAD + /NADH ratio, and intracellular pyruvate level are the driving forces for the switch from aerobic glycolytic metabolism to hyperoxidative metabolism in CHO cells, and changes in lactate levels vary with these parameters 44,45 . Usually, in the rapid glycolysis stage, the reducing power NADH is continuously generated, and the reduction of pyruvate to lactate can quickly balance the intracellular redox state to maintain the rate of glycolysis; when the rate of oxidative phosphorylation is rapid, intracellular NADH continuously enters the mitochondria to provide reducing power, and redox balance is then maintained by the consumption of lactate to produce NADH.…”
Section: Discussionmentioning
confidence: 99%
“…37 The NAD + /NADH ratio, and intracellular pyruvate level are the driving forces for the switch from aerobic glycolytic metabolism to hyperoxidative metabolism in CHO cells, and changes in lactate levels vary with these parameters. 44,45 Usually, in the rapid glycolysis stage, the reducing power NADH is continuously generated, and the reduction of pyruvate to lactate can quickly balance the intracellular redox state to maintain the rate of glycolysis; when the rate of oxidative phosphorylation is rapid, intracellular NADH continuously enters the mitochondria to provide reducing power, and redox balance is then maintained by the consumption of lactate to produce NADH. Therefore, it can be considered that the redox balance drives the consumption of lactate, which is consistent with our findings.…”
Section: Interactions Between Pyruvate Lactate Metabolism and Nad + /...mentioning
confidence: 99%